Padronização e aplicação do ensaio cometa para análise de genotoxicidade do mercúrio em abelhas da espécie Bombus atratus (Hymenoptera, Bombini) - Ceschi-Bertoli, Letícia (2020)
The mercury (Hg) is a non-essential trace metal, that is highly toxic to living beings, is a major contaminant of water bodies. Despite the genotoxic importance of Hg, there are no studies on its genotoxicity in native neotropical bees, using effective biomarkers. Therefore, a study of the genotoxicity of Hg in Bombus atratus bees was carried out through the comet assay. This assay determines the extent of DNA damage to individual cell nuclei by differential migration of DNA fragments in microelectrophoresis. Despite the effectiveness and sensitivity of the technique, there are no records in the literature about the applicability of this assay to Bombus neotropical bees, which have many endangered species. B. atratus workers were collected from Sorocaba, SP, (23º34'53.1''S 47º31'29.5'') during the months of February to March 2019. After capture, the workers were individually placed in special boxes for the toxicological test and kept in an incubator at 26 ºC, 70% humidity, in the dark, for 48 hours, according to OECD recommendations. Eleven workers were used for the group exposed to Hg at a concentration of 0.2 µg L -1, concentration considered safe by CONAMA (nº 357, 2005), and the same number for the control group. Both groups were maintained with a 70% sucrose solution. In addition to the exposed group, 0.2 µg L -1 Hg solution was offered, and to the control group, uncontaminated water. After 48 hours, the tissues that compose the Hepato-Nephrocytic System (HNS), dorsal vessel, hemocytes, fat body/pericardial cells, and Malpighi tubules (MT), were collected and processed for the comet assay. The results showed that Hg promoted genotoxicity in these animals. Regarding the control group, the HNS of workers exposed to Hg was sensitive to contamination due to the abundant presence of different levels of comets, which indicate the fragmentation of genetic material. While MT, in turn, were less responsive to the trace metal, presenting fewer damaged nuclei. Statistical analysis compared between level 0 and total damage parameters showed higher genotoxicity promoted by Hg in HNS of the exposed group, compared to the control group. While genotoxicity in MT was similar between control and exposed groups. Therefore, it can be concluded that HNS is more responsive to Hg exposure than MT. It was concluded that the concentration of Hg considered safe by CONAMA compromised the cells that compose the HNS, impairing the general physiology of the studied species, even if the TM were not affected.